2022
DOI: 10.3390/agriculture12050735
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Impact of Youth-in-Agribusiness Program on Poverty and Vulnerability to Poverty in Nigeria

Abstract: Poverty persists in many developing countries, including Nigeria, owing to inadequate infrastructure, unemployment, or poor working conditions, among other factors. Youth poverty and vulnerability to poverty have been identified to prevalent among the young population. Using an endogenous switching probit regression approach, in this study, we evaluated the impacts of youth participation in agribusiness programs (YIAPs) on poverty and vulnerability to poverty in Nigeria. Our findings revealed that some demogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 20 publications
(27 reference statements)
0
6
0
Order By: Relevance
“…For example, various programs have been implemented in Nigeria, such as the Youth in Agriculture Initiative (YIA), the N-Power Agro program, and the Growth Enhancement Support Scheme (GESS) [14]. These projects have shown promising outcomes in empowering young people and enhancing their sustainable livelihoods [70,88]. Furthermore, it is imperative that these programs have sufficient funding and actively interact with pertinent stakeholders, including youth and community leaders, to guarantee their appropriate design and implementation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…For example, various programs have been implemented in Nigeria, such as the Youth in Agriculture Initiative (YIA), the N-Power Agro program, and the Growth Enhancement Support Scheme (GESS) [14]. These projects have shown promising outcomes in empowering young people and enhancing their sustainable livelihoods [70,88]. Furthermore, it is imperative that these programs have sufficient funding and actively interact with pertinent stakeholders, including youth and community leaders, to guarantee their appropriate design and implementation.…”
Section: Discussionmentioning
confidence: 99%
“…Five studies [19,25,[70][71][72] focused on the role of information in influencing young people towards agribusiness. Some studies indicated that facilitating youth access to technology may increase engagement and productivity in the agriculture sector [71,72].…”
Section: Access To Technologymentioning
confidence: 99%
See 2 more Smart Citations
“…In developing countries, youth unemployment is a challenge and has received the increasing attention in policy formation (Bello, 2022). Africa faces constraints to increase rural economic growth which has the potential to create job opportunities.…”
Section: Introductionmentioning
confidence: 99%